Iris coloboma in one eye and pigment dispersion syndrome in the fellow eye. (22nd May 2013) - Galvis, Virgilio; Tello, Alejandro; Valarezo, Paul; Prada, Angélica M
Abstract : We report a case of a 43-year-old patient with coloboma of the iris, zonule, ciliary body, choroid and retina in the right eye and pigment dispersion syndrome in the left eye. Considering the hypothesis of the pigment dispersion syndrome pathogenesis in which a difference of pressures in the anterior and posterior chambers creates a posterior convexity of the iris leading to reverse pupillary block, iris touch and consequently causing pigment dispersion, we suggest that the presence of an iris coloboma, by equalising the pressures in the two chambers, prevented the onset of syndrome in that eye.